High tech startup creation for energy efficient built environment - Pacheco-Torgal, F. (2017)
The civil engineering area has long been known for not being associated with high tech startup creation. This is a sign of the low innovation which is confirmed by its low patenting level thus contributing to undermine the prestige of this area. Still this area has an important role to play given the environmental impacts of the construction industry that will be exacerbated in the next decades due to the growth in world population, each day there are about 220,000 new inhabitants which means more than 9,7 billion people by 2050 and 11,2 billion by 2100. A direct consequence of such growth relates to a steady increase of energy consumption which is the source of two-thirds of global greenhouse-gas emissions. The building sector is responsible for high energy consumption and its global demand is expected to grow in the next decades. Between 2010 and 2050 the global heating and cooling needs are expected to increase 70% in residential buildings and 90% in commercial buildings. Major energy efficiency measures are therefore crucial to reduce energy consumption and greenhouse-gas emissions of the building sector. This includes development of new technologies and materials to improve greatly energy efficiency. Since information derived from knowledge is critical for individuals to transform innovative ideas into commercial products and services, this paper reviews recent developments on nano and bio based innovations important for an energy efficient built environment. This review may contribute to enhance the innovation and patenting activity in civil engineering. This may help to foster the creation of high tech startups for an energy efficient built environment.